Pectic Galactan Polysaccharide‐Based Gene Delivery System for Targeting Neuroinflammation. (10th June 2021) - Buaron, Nitsa; Mangraviti, Antonella; Volpin, Francesco; Liu, Ann; Pedone, Mariangela; Sankey, Eric; Aranovich, Dina; Adar, Itay; Rodriguez, Fausto J.; Nyska, Abraham; Goldbart, Riki; Traitel, Tamar; et al.
Abstract: Treating neuroinflammation‐related injuries and disorders through manipulation of neuroinflammation functions is being heralded as a new therapeutic strategy. In this study, a novel pectic galactan (PG) polysaccharide based gene therapy approach is developed for targeting reactive gliosis in neuroinflammation. Galectin‐3 (Gal‐3) is a cell protein with a high affinity to β‐galactoside sugars and is highly expressed in reactive gliosis. Since PG carries galactans, it can target reactive gliosis via specific carbohydrate interaction between galactan and Gal‐3 on the cell membrane, and therefore can be utilized as a carrier for delivering genes to these cells. The carrier is synthesized by modifying quaternary ammonium groups on the PG. The resulting quaternized PG (QPG) is found to form complexes with plasmid DNA with a mean diameter of 100 nm and have the characteristics required for targeted gene therapy. The complexes efficiently condense large amounts of plasmid per particle and successfully bind to Gal‐3. The in vivo study shows that the complexes are biocompatible and safe for administration and can selectively transfect reactive glial cells of an induced cortical lesion. The results confirm that this PG‐based delivery system is a promising platform for targeting Gal‐3 overexpressing neuroinflammation cells for treating neuroinflammation‐related injuries and neurodegenerative diseases. Abstract : A pectic galactan‐based delivery system is developed aiming to target Galectin‐3 overexpressing cells as found in neuroinflammation specifically. The developed system displays ability to selectively transfect neuroinflammation cells of an induced cortical lesion in vivo. Therefore, it can serve as a new therapeutic strategy for delivering genetic factors, pro/anti‐inflammation agents to modulate neuroinflammation for treating central nervous system injuries and neurodegenerative diseases.